Bonaventure on the beatific vision: A response to Hans Boersma - Page, Kaylie (Scottish journal of theology, 2025)
This paper considers Hans Boersma's analysis of Bonaventure's account of the beatific vision in his book Seeing God: The Beatific Vision in Christian Tradition. Boersma disputes Bonaventure's claim in his Itinerarium Mentis in Deum that mystical union with God in this life takes place via the will and not the intellect, arguing that union with God must always produce union of the intellect and will. However, Boersma's consideration of the Itinerarium fails to take into account Bonaventure's other works, particularly his Commentary on the Gospel of John, in which he states that the beatific vision does unify the intellect and will, but that sin's effect on the faculties makes the intellect unable to experience union with God in this life. This closer look at Bonaventure's thought shows that Boersma needs a stronger account of the intellect and will to critique Bonaventure effectively.